EFFECT OF NASAL CORTICOSTEROIDS ON OXIDATIVE STRESS PARAMETERS IN CHILDREN WITH ALLERGIC RHINITS - Arnaudova Danevska, Ivana; Jakjovska, Tatjana; Atanasovska, Emilija; Petrusevska, Marija; Dzekova-Vidimliski, Pavlina; Krstevska Balkanov, Svetlana; Balkanov, Trajan; Zendelovska, Dragica (Journal of Morphological Sciences, 2023)
Oxidative stress (OS) is a result of an imbalance between the production of free radicals and the antioxidant defense mechanisms in the organism. Allergic rhinitis (AR) is characterized by chronic inflammation and increased presence of eosinophils, basophils and mast cells in nasal secretions and mucosa. Stimulation of these cells results in production of free radicals (reactive oxygen metabolites). The aim of this study was to determine the level of OS and antioxidant capacity in children with AR after 8 weeks treatment with nasal corticosteroid (NCS). Thirty children with AR (mean age 8.3 ± 2.9 years) were included. The FRAS 5 Bravo system was used to determine the OS parameters. Demographic characteristics, medical history, children's living conditions and eating habits were obtained from the questionarrie. Anthropometric measurements, absolute number of eosinophils in the peripheral smear and eosinophils in nasal smear were performed in each child. The mean value of blood concentration of serum peroxides (d-ROMs) was 403.4 ± 91.3 U. Carr, while the mean value of OS index was 95.1 ± 45.9. After 8 weeks of treatment with NCS, the mean values were 337.6 ± 71.9 U. Carr, and 53.6 ± 28.3, respectively. Both parameters had significantly lower values (p<0.05) compared to those before the initiation of NCS therapy. After treatment, a significant improvement in the symptoms score of AR was detected (p<0.05). NCS therapy makes asignificant improvement of the symptoms and a considerable reduction in the OS in children with AR. Keywords: allergic rhinitis, children, oxidative stress, d-ROMs, PAT, OSI https://doi.org/10.55302/JMS236101ad